Immunology - Lydyard, Peter M.; Whelan, A.; Fanger, Michael W.; Lydyard, Peter M. (New York : Garland Science, 2011)
"BIOS Instant Notes in Immunology, Third Edition, is the perfect text for undergraduates looking for a concise introduction to the subject, or a study guide to use before examinations. Each topic begins with a summary of essential facts-an ideal revision checklist-followed by a description of the subject that focuses on core information, with clear, simple diagrams that are easy for students to understand and recall in essays and exams"--
A. Overview of the immune systemB. Cells and molecules of the innate immune systemC. The adaptive immune systemD. AntibodiesE. The antibody responseF. The T cell response - cell-mediated immunityG. Regulation of the immune responseH. Immunity to infectionI. VaccinationJ. Immunodeficiency - when the immune system failsK. Hypersensitivity - when the immune system misbehavesL. Autoimmunity and autoimmune diseasesM. TransplantationN. Tumor immunologyO. Gender and the immune systemP. Aging and the immune system (immunosenescence)Q. Immunotherapy
Rev. ed. of: Instant notes in immunology. 2003.
Includes bibliographical references and index.
Keywords: Immunology -- Outlines, syllabi, etc; Immunity -- Oulines, syllabi, etc